2021
DOI: 10.1007/s10517-021-05331-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Marker System for Early Diagnosis of Breast Cancer

Abstract: Changes in the methylation levels of 21 microRNA genes in 91 breast cancer samples in comparison with paired samples of histologically unchanged tissue were studied by quantitative methylation-specific PCR. For 19 microRNA genes, a significant increase in the methylation level in tumors in comparison with normal tissues was shown (Mann-Whitney test). When considering the data for breast cancer samples only from patients with clinical stages I and II (59samples), 17 genes with a significantly increased level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…There is limited information about the significance of DNA hypermethylation of the remaining biomarkers. Recent studies showed that the differential expression and DNA methylation pattern of these genes may be used as diagnostic and prognostic biomarkers for different types of cancer, e.g., breast cancer (NRIP3 [44], MIR129-2 [45,46]), hepatocellular carcinoma (SOX8 [47]), oesophageal cancer (MIR129-2 [48]), lung cancer (MIR129-2 [49]), and colorectal cancer (MIR129-2 [50,51]). Interestingly, the SOX gene family is generally discussed as having oncogenic properties and SOX overexpression can be associated with poor prognosis [52].…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information about the significance of DNA hypermethylation of the remaining biomarkers. Recent studies showed that the differential expression and DNA methylation pattern of these genes may be used as diagnostic and prognostic biomarkers for different types of cancer, e.g., breast cancer (NRIP3 [44], MIR129-2 [45,46]), hepatocellular carcinoma (SOX8 [47]), oesophageal cancer (MIR129-2 [48]), lung cancer (MIR129-2 [49]), and colorectal cancer (MIR129-2 [50,51]). Interestingly, the SOX gene family is generally discussed as having oncogenic properties and SOX overexpression can be associated with poor prognosis [52].…”
Section: Discussionmentioning
confidence: 99%